PENDAMPINGAN PEMBUATAN MEDIA PEMBELAJARAN STEM-PBL BERBASIS ARTIFICIAL INTELLIGENT (AI) UNTUK MGMP KIMIA SMA KABUPATEN DELI SERDANG - Sari, Dwy Puspita; Dibyantini, Ratu Evina; Silitonga, Agnes Irene; Nst, Mutiara Agustina; Ardila, Mutia (Bajang Institute, 2025)
This activity aimed to enhance partners’ expertise in developing AI-based STEM-PBL learning materials, thereby advancing education, science, technology, and human resource development. It also provided training, technology application, and support to improve the quality of education through innovative learning media. Key issues identified included teachers’ low motivation to create technology-based resources, students’ lack of enthusiasm, limited technology use in chemistry classes, and teachers’ insufficient skills in utilizing digital tools. To address these challenges, strategies such as socialization, training, technology deployment, mentorship, and evaluation were implemented. These efforts focused on encouraging teachers and students to engage in problem-solving and innovative learning practices. The program’s effectiveness was reflected in the improvement of participants’ understanding, shown by an increase in the mean pretest score (51.43) to the posttest score (79.13). Thus, the objectives of enhancing mastery of the material and applying knowledge in practice were successfully achieved.